Peningkatan Wawasan Petani Tambak Udang melalui Sosialisasi Pengelolaan Kualitas Air di Desa Kurau Kabupaten Bangka Tengah - Notonegoro, Hartoyo; Pratiwi, Fika Dewi; Zulkia, Dwi Rizka (LPPPM STAI Darul Hikmah Bangkalan, 2022)
Kurau Village is one of the villages in Central Bangka Regency, Bangka Belitung Islands. The potential being developed in this village is people-scale shrimp ponds. One of these shrimp ponds is a group of vaname shrimp cultivators named Pokdakan Gempa 01. Pokdakan Gempa 01 cultivator group is relatively new because it was established in 2021 and there is still little knowledge about water quality management. Management of water quality in ponds is very important to increase the amount of shrimp productivity and minimize shrimp stress due to abnormal water quality conditions. Therefore, community empowerment programs are needed in order to increase community knowledge and increase productivity. The method used in empowering water quality management is a combination of counseling methods, mentoring and active community participation. At the end of the extension activities, an evaluation was held in the form of a Likert scale questionnaire (1-4), to measure partner satisfaction and the usefulness of the insights provided. Based on the results of the evaluation, it was found that the socialization carried out added insight to partners and was useful because it was in accordance with the needs of partners and the desire for sustainability of service activities from partners.